Criticism of Religious Moderation in Ahmadiyah Recognition(Case Study of Religious Freedom in Indonesia) - Khoiru Nisa, Akhmala Wulan; Arif Nur Roqim; Hikma Malja’a Shulha; Aditia Muhammad Noor (Nizham Jurnal Studi Keislaman, 2024)
Indonesia as a country with a diversity of religions and the highest Muslim population applies freedom of religion (Religious Fredoom). One of the minority groups in Indonesia is Ahmadiyah, its existence often faces discrimination and challenges. The rejection of Ahmadiyya was due to a different reformation teaching and the majority of Muslims considered the teachings brought by Ahmadiyah to deviate from Islamic guidelines. Writing this article is to analyze an argument regarding religious moderation in the recognition of Ahmadiyya. This research was conducted on March 28, 2023. In this study, a qualitative descriptive method was used based on a case study of religious freedom. The data written in this study were obtained from relevant sources such as literature, articles and documents related to Ahmadiyya in Indonesia. Criticism of religious moderation in this context refers to criticism of the actions of the government or religious leaders which limit the religious freedom of Ahmadiyah. Religious moderation itself can be interpreted as an approach that seeks harmony between various religions and beliefs, but in some cases, moderation can lead to restrictions on the freedom of religion of minority groups.